1988
DOI: 10.1002/j.1460-2075.1988.tb03206.x
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of 5′-nucleotidase in a rat hepatoma cell line.

Abstract: Intracellular movement of cell surface 5′‐nucleotidase was studied in H4S cells, a rat hepatoma cell line. Surface labelled cells were incubated for various periods at 37 degrees C and treated with neuraminidase at 0 degrees C. Removal of sialic acid residues from glycoproteins results in a change of their isoelectric points. Analysis with isoelectric focusing was then used to distinguish between cell surface and intracellular 5′‐nucleotidase. Incubation of 125I‐surface‐labelled cells at 37 degrees C resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…A significant amount of CD73 was detected on the B16F10 cell surface by immunofluorescence; however, its main localization pattern appeared to be intracellular. This is in agreement with an earlier hypothesis stating that an extensive intracellular distribution of CD73 is present in a membrane-bound pool (i.e., lysosomes, Golgi apparatus and transcytotic vesicles) and that CD73 undergoes continual exchange between the plasmatic and internal membranes (1,32,33). We encountered a problem detecting CD73 on the surface of non-fixed B16F10 and HEK293T cells by flow cytometry (although the intracellular antigen was apparent in the fixed cells), but this might be due to ecto-domain shedding after binding of the anti-CD73 antibody.…”
Section: Discussionsupporting
confidence: 93%
“…A significant amount of CD73 was detected on the B16F10 cell surface by immunofluorescence; however, its main localization pattern appeared to be intracellular. This is in agreement with an earlier hypothesis stating that an extensive intracellular distribution of CD73 is present in a membrane-bound pool (i.e., lysosomes, Golgi apparatus and transcytotic vesicles) and that CD73 undergoes continual exchange between the plasmatic and internal membranes (1,32,33). We encountered a problem detecting CD73 on the surface of non-fixed B16F10 and HEK293T cells by flow cytometry (although the intracellular antigen was apparent in the fixed cells), but this might be due to ecto-domain shedding after binding of the anti-CD73 antibody.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the observed difference between membrane-bound Fe for cells with and without p97 and that only 45% of p97 is removed by the pronase treatment, it appears that one molecule of p97 is able to bind one atom of Fe, which supports the conclusions of other studies (Baker et al, 1987). Previous studies have demonstrated that GPI-anchored proteins can be internalized and recycled back to the cell surface (van den Bosch et al, 1988;Tausk et al, 1989;Lemansky et al, 1990;Keller et al, 1992). The binding of Fe to p97 and the internalization of Fe is consistent with a GPI-anchored protein being involved in the binding and internalization of a ligand.…”
Section: Discussionsupporting
confidence: 83%
“…A similar analysis (average values from five fields) of the coclustering of Thy-1 and folate receptors on G3G2 cells showed that -35% of the folate receptor clusters contained detectable Thy-1 (random colocalization value of 12%) and -55% of Thy-1 clusters contained detectable folate receptor (random colocalization value of -10%). Thus, although GPI-anchored protein monomers Im l l o o f f i j o , now that the major pathway of internalization of the folate receptor is by way of bulk membrane endocytosis (12, 13) mediated by clathrin-dependent and independent pathways (14), similar to the pathway of other GPI-anchored proteins (15,16). Previous reports that GPI-anchored proteins are excluded from coated pits (16,17) may be explained by the ability of GPI-anchored proteins to redistribute to caveolae artifactually during the process of immunolocalization, thereby apparently depleting coated pits of GPI-anchored proteins.…”
Section: Experimentioning
confidence: 98%